CARE MANAGEMENT PROCESS IN APPENDECTOMY NURSING - Luca, Ana (European Scientific Journal, ESJ, 2014)
The First appendectomy was made by Claudius Amyand, surgeon at Westminster and St. George’s Hospitals, who operated in 1736 a 11 year old boy with a scrotal hernia fistulae. During the intervention he found a perforated appendix by a needle. He risked almost all the appendix, which resulted in the recovery of the patient. In 1755 Heister concluded that Appendix may be the site of a primary acute inflammation based on the dissection of a criminal. Loyer-Villermany In 1824 introduced in the royal academy of medicine in Paris two cases with acute appendicitis that led to death. In both cases, the autopsy found black appendix while cecum was less affected. Three years later these observations were confirmed by Milier.Husson & Dance articles in 1827, Goldback 1830 and on all Dupuytren in 1935 that discovered the concept of an inflammation, developed by adipose tissue, which surrounds cecum.